Systematic Changes in Preference for Schedule-Thinning Arrangements as a Function of Relative Reinforcement Density. Issue 4 (July 2018) - Briggs, Adam M.; Akers, Jessica S.; Greer, Brian D.; Fisher, Wayne W.; Retzlaff, Billie J.
We treated destructive behavior maintained by both social-positive (i.e., access to tangibles) and social-negative (i.e., escape from demands) reinforcement in an individual diagnosed with autism spectrum disorder using functional communication training (FCT). We then thinned the schedule of reinforcement for the tangible function using a multiple schedule (mult FCT) and later thinned the availability of escape using a chained schedule (chain FCT). Both treatments proved effective at maintaining functional communicative responses while decreasing destructive behavior to near-zero levels. In addition, treatment effects maintained when we rapidly thinned mult FCT to the terminal schedule. Throughout chain-FCT schedule thinning, we assessed client preference for each schedule-thinning arrangement (mult FCT or chain FCT) using a concurrent-chains procedure. Client preference reliably shifted from chain FCT to mult FCT as the response requirement increased and the proportion of session spent in reinforcement began to favor mult FCT. We discuss the clinical implications of these findings.